DOES CHILDHOOD FATHER INVOLVEMENT FOSTER TRANSFORMATIONAL LEADERSHIP? EVIDENCE FROM MEDIATION MODEL ATTACHMENT - Eunike Chintya Laura; Hasna; Pratiwi Kuswardani (RADJA PUBLIKA, 2026)
Transformational leadership is increasingly recognized as a critical competency in contemporary organizations, yet its developmental antecedents remain insufficiently understood. Although father involvement has been linked to positive psychosocial outcomes, the psychological mechanism through which early paternal caregiving contributes to transformational leadership has received limited empirical attention. This study examined the role of attachment in the association between father involvement and transformational leadership among emerging and young adults. A quantitative explanatory correlational design was employed with 310 participants aged 20–40 years who had prior leadership experience. Data were collected using the Father Involvement Scale (FIS), Experiences in Close Relationships-Revised (ECR-R), and Transformational Leadership Inventory (TLI) and analyzed using mediation analysis with a bootstrapping approach. The findings revealed that father involvement was directly associated with transformational leadership, while attachment was also associated with transformational leadership. However, attachment did not mediate the association between father involvement and transformational leadership. These findings suggest that the developmental influence of father involvement on transformational leadership may operate through alternative pathways beyond attachment, such as self-regulation, socio-emotional competence, resilience, and social learning. This study contributes to developmental and organizational psychology by providing a more comprehensive understanding of how early paternal caregiving experiences shape transformational leadership in adulthood.